Komposisi Gastropoda di Hutan Mangrove Pulau Sepok Keladi Kabupaten Kubu Raya Kalimantan Barat - Tri Rima Setyawati, Habil Algifari, Junardi (Universitas Tanjungpura, 2019)
Gastropods are an invertebrata which has an important role as an indicator quality mangrove forest. The presence of Gastropods in Sepok Keladi mangrove forest was decreasing due the habitat degradation and it impact on the Gastropods community. The purpose of this research is to determine the diversity of Gastropod species in mangrove forest Sepok Keladi Island Kakap River District Kubu Raya Regency. This study uses purposive random sampling method at six different stations with two 5x5m2 size plots in each station and four replication. The study found four families of Gastropods, i.e. Ellobidae, Littorinidae, Neritidae and Potamidiidae. Epifauna Gastropods found nine species and are five of them are treefauna. The most species foundy Cerethidae obtusa from Potamididae family.